KEPADUAN UNSUR VERBAL DAN NONVERBAL DALAM MEME INSTAGRAM BERBAHASA ARAB: ANALISIS WACANA - Masrukhi, Moh. (Jurnal CMES, 2018)
Meme Instagram generally uses two views, as well as verbal and nonverbal text. This article will reveal the verbal and nonverbal structure of the Instagram meme. The aim is to find out what are the elements of meme its pattern and how the interrelationships between these elements are interrelated and aligned together into one unit. The meme data is taken from the @Mzajeat instagram and @Iq.Shabab which is in Arabic. Furthermore, the data is analyzed by utilizing concepts or theories of discourse and semantics. The result is the opening element of memes can be verbal or nonverbal elements, as well as the body or contents of memes can be in the form of verbal or nonverbal elements. From this research, it can be argued that the integration or linkage and the existence of these two elements make memes a discourse that is very interesting and very diverse in interpretation, especially on nonverbal elements. Through these two elements the meaning and message of the meme writer can be conveyed.